Translation Elongation Factor 1-Alpha Sequencing Provides Reliable Tool for Identification of Fusarium graminearum Species Complex Members - Yörük, Emre; Yli-Mattila, Tapani (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The Fusarium graminearum species complex (FGSC) is a worldwide phytopathogenic fungus of small grain cereals. Genetics and bioinformatics tools have been providing an efficient strategy for identifying FGSC. However, the potential reliability of tef1−α sequencing in FGSC members has not been well investigated. In this study, the tef1−α sequencing data of 246 FGSC members, one F. culmorum, and one F. solani isolate were subjected to distance-, character-, and PCA-based phylogenetic analysis. Linux terminals and the R programming language were used in phylogenetic analysis. The Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and maximum likelihood methods produced relatively more homogenous F. graminearum sensu stricto (Fgss) and F. asiaticum isolates. Fgss and F. asiaticum isolates co-clustered in two separate sub-divisions in the ML and UPGMA methods, with significant differences in the Chi2 test (p < 0.05). PCA profiling revealed a low level of variation in FGSC members, with 99–99.5% percentages in axis 1. An increased number of taxa and isolates would be tested for tef1−α in future studies. To our knowledge, this is also the first study to combine phylogenetic methods with PCA tests for comprehensive characterization of FGSC members.